2015
DOI: 10.1021/acs.chemmater.5b00697
|View full text |Cite
|
Sign up to set email alerts
|

Diameter-Controlled Germanium Nanowires with Lamellar Twinning and Polytypes

Abstract: Type of publicationArticle (peer-reviewed) Link to publisher's versionhttp://pubs.acs.org/journal/cmatex http://dx.doi.org/10.1021/acs.chemmater.5b00697Access to the full text of the published version may require a subscription. are appealing for use in nanowire devices. This paper details the influence of colloidal magnetite iron oxide nanoparticle seeds to regulate the radial dimension and twin boundary formation in Ge nanowires grown through a liquid-injection chemical vapor deposition process. Control over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 63 publications
(156 reference statements)
5
30
0
Order By: Relevance
“…In group IV NWs the formation of different crystal phases is a rather common phenomenon and most nanowire growth schemes produces a rather random sequence of polytypes, with a high density of various stacking defects. However, recent results go even further by showing that the presence of hexagonal ordered phases as atomic stacking in cubic domains (homojunctions) can be controlled [37,38].…”
Section: Surface Reconstruction and Facet Arrangementmentioning
confidence: 99%
“…In group IV NWs the formation of different crystal phases is a rather common phenomenon and most nanowire growth schemes produces a rather random sequence of polytypes, with a high density of various stacking defects. However, recent results go even further by showing that the presence of hexagonal ordered phases as atomic stacking in cubic domains (homojunctions) can be controlled [37,38].…”
Section: Surface Reconstruction and Facet Arrangementmentioning
confidence: 99%
“…Recently we were successful in implementing controlled crystal imperfections, mainly in the form of twinning defects in both axial and radial direction, in Ge nanowire via catalyst engineering in a three phase nanowire growth. [28,29] An "epitaxial defect transfer" process and catalyst-nanowire interfacial engineering was employed to induce twin defects parallel and perpendicular to the nanowire growth axis. For impurity injection and engineering, a third-party metal catalyst was used to guide the non-equilibrium incorporation of Sn adatoms into the precipitated Ge bilayers, during Ge nanowire growth, where the impurity Sn atoms become trapped with the deposition of successive layers, thus giving an extraordinary Sn content in the alloy nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…Controlled transverse twin formation in Ge nanowire was initiated through the use of new growth promoter such as patterned hemispherical magnetite nanodots. [29] These particular magnetite nanodot catalysts were suitable, due to the particular curvature of the catalyst-substrate and catalyst-nanowire interface and the adherence of the patterned nanodots with a substrate, to promote the growth of large numbers of <111> oriented Ge nanowires with lateral growth of twin planes perpendicular to the nanowire growth axis (Figure 3a). A 60° rotation of crystal orientation on both sides of the twin planes with the growth axis represents a mirror reflection of a 3C stacking order of the {111} planes without any bond-breakage at the interface (Figure 3b).…”
mentioning
confidence: 99%
“…[6][7][8] Nevertheless, in group IV nanowires, the stability of novel polytypes -previously theoretically predicted 9 but experimentally observed only very locally in the form of crystal imperfections [10][11][12][13] is now supported by clear experimental evidences. [14][15][16][17][18][19] For instance, Vincent et al 14 reported the synthesis of quasi-periodic allotrope Ge heterostructures of hexagonal-diamond (wurtzite structure with single atom type) and cubic-diamond domains. These systems were obtained by a straininduced phase transformation in which size effects (in particular the preferential nucleation of dislocations on the wire surface and the activation of unusual slip planes) play a crucial role by lowering the value of the stress required by the cubic to hexagonal transition.…”
mentioning
confidence: 99%